American Democracy and Governance in a Polarized Era - Barringer, Richard (Maine Policy Review, 2021)
Where do we stand today amid America’s sharply divided politics and governance? I argue here that in less than two and a half centuries since the nation’s founding, it has gone from the espousal of democracy and the general welfare to the pursuit of autocracy and corporatism. In the absence of fundamental reforms, America’s founding principles and our national character are at risk.